Glycerol metabolism of haloarchaea. (13th November 2016) - Williams, Timothy J.; Allen, Michelle; Tschitschko, Bernhard; Cavicchioli, Ricardo
Summary: Haloarchaea are heterotrophic members of the Archaea that thrive in hypersaline environments, often feeding off the glycerol that is produced as an osmolyte by eucaryotic Dunaliella during primary production. In this study we analyzed glycerol metabolism genes in closed genomes of haloarchaea and examined published data describing the growth properties of haloarchaea and experimental data for the enzymes involved. By integrating the genomic data with knowledge from the literature, we derived an understanding of the ecophysiology and evolutionary properties of glycerol catabolic pathways in haloarchaea.